Communication Strategies of “Sicredi Região Centro RS/MG” in the Digital Environment - Knoll, Graziela Frainer; Piccin, Laura Pegoraro (Cadernos de Educação Tecnologia e Sociedade, 2021)
The general objective of this research was to analyze the digital presence of Sicredi through its communication strategies in social media. As specific objectives, we sought to: map the digital presence of Sicredi Região Centro RS/MG in social media; identify the communication strategies used by the cooperative on Facebook and Instagram; gauge the level of engagement of your followers in the selected sample, and ascertain the brand's digital presence level on Facebook and Instagram. This was done with a qualitative-quantitative research method of descriptive analysis, with postings collected from social media of the brand in 2018. With this, it can be concluded that although the level of engagement is low, the cooperative worries about being inserted in social media and in producing content focused on the relationship phase with its followers.